UUMKL former director Mohd Yusof appointed Kuin rector - Borneo Post, (KK) (Borneo Post (KK), 2013)
ALOR SETAR: Universiti Utara Malaysia Kuala Lumpur (UUMKL) former director Prof Datuk Mohd Yusof Kasim was appointed Insaniah University College (Kuin) rector effective Monday. Kedah Menteri Besar Datuk Mukhriz Tun Dr Mahathir said the appointment of Mohd Yusof, who was previously Asia-Pacific University College of Technology and Innovation vice-chancellor, was made after a painstaking process to avoid any harm to stakeholders.